The Influence Of Twitter Social Media As A Social Campaign Media For Environmental Care Movements On Plastic Brand Twitter Users - Dwi Laras Karimah; Aulia Ilma Kusumaningtyas; Jonathan Alexander Citra; Ricardo Indra (Publikasi Indonesia, 2023)
Environmental damage caused by the use of plastic occurs because, in everyday life, people cannot be separated from the use of plastic. Humans feel the effects caused by plastic waste, and other living things, such as animals, also feel this loss. Several initiatives have been proposed to reduce excessive plastic use, including a digital campaign by AMDK on social media and Twitter. So, this study was conducted to determine whether campaigns carried out through social media, such as Twitter, are a form of positive movement and can be known by all consumers. The research method used in this study is quantitative, with survey methods using 100 samples of active Twitter users. Data is processed using data analysis techniques. Data is processed using data analysis techniques using the Structural Equation Model (SEM). The results of this study show that the two dependent variables, namely social campaigns and social media, have a positive effect on the independent variable, namely brand image